Gone : a study of the demise of technical high schools in New Zealand : including a case study of the transition of Palmerston North Technical High School into Queen Elizabeth College : a research exercise presented in partial fulfilment of the requirement for the Bachelor of Arts with Honours in History at Massey University - Body, E. W. (Edward W.) (Massey University, 2010)
This study assesses the impact of 'comprehensive education' in New Zealand in the short and long term, together with the increase of school leaving age to fifteen, on post-primary schools, and in particular, on Palmerston North Technical High School and its transition to Queen Elizabeth College. [From Introduction]